Architektura dworu i pałacu w Przytoku = Architecture of the manor house and palace in Przytok - Adamek-Pujszo, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the past there were two noble residences in Przytok: late-Renaissance manor house (non-existed) and Neo-Renaissance palace. From descriptions by F.A. Zimmermann (1791) and O. Frühbus (1841) it appears that the manor house, erected between 1596 and 1597 by Joachim von Stentsch, was made up with main body and a wing, so the building had a plan of "L" letter. There were a portal on the front elevation and gables above the elevations.
Keywords: Przytok (pow. zielonogórski) - historia; dwór; pałac; architektura późnorenesansowa; Dolny Śląsk - architektura; portal; neorenesans; Stentsch, Joachim von; Mesar, Anthonius von; Kraker-Schwarzenfeld, Emil von; Jaekel, Adolph Theodor; Lüdecke, Carl; Biechów; Siedlisko (woj. lubuskie); Schwerin; manor house; palace; late-Renaissance architecture; neo-Renaissance